Analysis of Subsurface Structure of Sembalun Geothermal Prospect Area, East Lombok with 2D and 3D Gravity Modeling - Nanda Ridki Permana; Belista Gunawan; Muhammad Nafian (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2022)
Abstract. The existence of Indonesian geothermal is estimated to be spread in 331 locations, one of which is Sembalun, East Lombok Regency. Therefore, this study was conducted to analyze the subsurface structure of geothermal prospect areas in the area using gravity methods. Gravity data used is satellite data as much as 4275 measurement points that have been corrected free air (FAA). The data processing stage resulted in a Complete Bouguer Anomaly (CBA) map with low anomaly values to be the target of research ranging from 58.9 – 115.7 mGal located in the east (Sembalun-Bumbung) and northeast (Sembalun-Lawang). The prospect of geothermal is controlled by the Talaga fault and Pusuk fault on the caldera floor (Sembalun-Lawang). In addition, the Tanakiabang fault and the Orok fault are near the manifestation of Sebau Hot Springs and on the Caldera floor (Sembalun-Bumbung). The results of 2D modeling correlated with 3D modeling conducted inversions showed geothermal sources are estimated to have a density of 2.68 gr/cc – 3 gr/cc consisting of hornblende andesite lava rocks with a depth of >2500, reservoir layer in the form of sand that has a density of 1.4 gr/cc - 1.72 gr/cc with a depth of 700 - 1200 m and a layer of a hood in the form of alluvium rocks that have a density of 1.8 gr/cc - 2.2 gr/cc with a depth of 0 - 500 m.